In Vivo Instability of (177)Lu-DOTATATE During Peptide Receptor Radionuclide Therapy - Lubberink, Mark (J Nucl Med, 2020)
Peptide receptor radiotherapy using (177)Lu-labeled somatostatin ligand analogs is a well-established treatment for neuroendocrine tumors, with (177)Lu-DOTATATE having acquired marketing authorization in Europe and the United States. The investigation of the pharmacokinetics of these radiopharmaceuticals in vivo in humans is crucial for personalized treatment management and understanding of treatment effects. Such an investigation requires input data on the in vivo stability of the radiopharmaceuticals in blood and plasma. The work presented here is devoted to the investigation of the in vivo stability of (177)Lu-DOTATATE in humans affected by neuroendocrine tumors. Methods: Blood samples of 6 patients undergoing (177)Lu-DOTATATE were taken at 0.5, 4, 24, and 96 h after injection. Analysis of metabolic stability was performed using high-performance liquid chromatography. Results: A fast metabolism of the radiopharmaceutical was observed, with the fraction of intact (177)Lu-DOTATATE in plasma decreasing rapidly to 23% ± 5% (mean ± SD) at 24 h and 1.7% ±0. 9% at 96 h after injection. Conclusion: The in vivo stability of (177)Lu-DOTATATE is much lower than previously assumed, with the major part of radioactivity in plasma consisting of (177)Lu-labeled metabolites already at 24 h after injection.